Coping With Intimate Partner Violence: The Effect Of Women’s Resources On Their Response To Violence In Turkey - BEŞPINAR, LÜTFİYE ZEYNEP (My University, 2024)
Abstract: The aim of this study is to investigate the interaction between the personal and social resources of women who have experienced intimate partner violence (IPV) and their responses to two specific types of violence, namely; physical and sexual violence. The study utilizes survey data from the \"2014 Domestic Violence against Women in Turkey Survey\", a follow-up to the 2008 nationwide survey on violence against women, which includes a wide range of socio-demographic background questions as well as questions on IPV and various types of violence against women and girls. This quantitative research represents one of the rare studies focusing on women\"s individual and institutional responses to IPV and it is also based on findings from the most recent field study on Domestic Violence against Women in Turkey. The sample design of the research is a multi-staged stratified cluster sampling and 11,247 households completed the survey from 12 statistical regions, urban and rural areas of Turkey. During the field visits, 13,310 women were identified as eligible for interviews, and 8,960 women were approached for face-to-face interviews. The response rate for the women interviews was recorded at 83.3 percent. Multinomial logit models were employed to elucidate the relationship between the responses of women who had been subjected to violence and their individual resources. The findings of the study reveal that individual resources such as age, higher education, urban residence, and being in regular employment with social security significantly increase the likelihood that women will engage in at least one institutional or non-institutional response to IPV.

Bu çalışmanın amacı, eş/yakın partner şiddeti (IPV) yaşamış kadınların kişisel ve sosyal kaynakları ile iki spesifik şiddet türüne (fiziksel ve cinsel şiddet) verdikleri tepkiler arasındaki etkileşimi araştırmaktır. Çalışmada, 2008 yılında ülke çapında yapılan kadına yönelik şiddet araştırmasının devamı niteliğinde olan ve IPV ile kadınlara ve kız çocuklarına yönelik çeşitli şiddet türlerinin yanı sıra çok çeşitli sosyodemografik arka plan sorularını da içeren "2014 Türkiye'de Kadına Yönelik Aile İçi Şiddet Araştırması" anket verileri kullanılmıştır. Bu nicel araştırma, Türkiye’de kadınların IPV'ye verdikleri bireysel ve kurumsal tepkilere odaklanan nadir çalışmalardan birini temsil etmektedir ve aynı zamanda bu konuda “Türkiye'de Kadına Yönelik Aile İçi Şiddet Araştırması”’nın en son yürütülen sahasından elde edilen bulgulara dayanmaktadır. Araştırmanın örneklem tasarımı çok aşamalı tabakalı küme örneklemesidir ve Türkiye'nin 12 istatistiki bölgesinden, kentsel ve kırsal alanlarından 11.247 hane anketi tamamlamıştır. Saha ziyaretleri sırasında 13.310 kadının görüşme için uygun olduğu tespit edilmiş ve 8.960 kadınla yüz yüze görüşme yapılmıştır. Kadınlarla yapılan görüşmelerde yanıt oranı yüzde 83,3'tür. Şiddete maruz kalmış kadınların yanıtları ile bireysel kaynakları arasındaki ilişkiyi açıklamak için multinomial logit modelleri gerçekleştirilmiştir. Araştırmanın bulguları, yaş, yüksek öğrenim, kentte ikamet etme ve sosyal güvencesi olan düzenli bir işte çalışma gibi bireysel kaynakların, kadınların IPV'ye karşı en az bir kurumsal veya kurumsal olmayan tepki verme olasılığını önemli ölçüde artırdığını ortaya koymaktadır. Anahtar Kelimeler: Yakın Partner Şiddeti, Kadına Karşı Şiddet, Kurumsal Destek Alma, Kadınların Kaynakları, Şiddetle Mücadele Stratejileri
Yakın Partner Şiddetiyle Başa Çıkmak: Türkiye'de Kadınların Sahip Oldukları Kaynakların Şiddete Verdikleri Tepkilere Etkisi
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); IPV (Intimate Partner Violence); Violence Against Women; Institutional Help-Seeking; Women’s Resources; Women’s Strategies to Fight Against Domestic Violence; Yakın Partner Şiddeti; Kadına Karşı Şiddet; Kurumsal Destek Alma; Kadınların Kaynakları; Şiddetle Mücadele Stratejileri